Average Error: 0.0 → 0.0
Time: 6.2s
Precision: 64
$\left(s + c \cdot s1\right) - s2$
$\left(s + c \cdot s1\right) - s2$
\left(s + c \cdot s1\right) - s2
\left(s + c \cdot s1\right) - s2
double f(double s, double c, double s1, double s2) {
double r535827 = s;
double r535828 = c;
double r535829 = s1;
double r535830 = r535828 * r535829;
double r535831 = r535827 + r535830;
double r535832 = s2;
double r535833 = r535831 - r535832;
return r535833;
}


double f(double s, double c, double s1, double s2) {
double r535834 = s;
double r535835 = c;
double r535836 = s1;
double r535837 = r535835 * r535836;
double r535838 = r535834 + r535837;
double r535839 = s2;
double r535840 = r535838 - r535839;
return r535840;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$\left(s + c \cdot s1\right) - s2$
2. Final simplification0.0

$\leadsto \left(s + c \cdot s1\right) - s2$

# Reproduce

herbie shell --seed 1
(FPCore (s c s1 s2)
:name "s + c * s1 - s2"
:precision binary64
(- (+ s (* c s1)) s2))